Influences of edaphoclimatic conditions on deep rooting and soil water availability in Brazilian Eucalyptus plantations - Evangelista Silva, Vinicius [UNESP]; Nogueira, Thiago Assis Rodrigues [UNESP]; Abreu-Junior, Cassio Hamilton; He, Zhenli; Buzetti, Salatier [UNESP]; Laclau, Jean-Paul [UNESP]; Teixeira Filho, Marcelo Carvalho Minhoto [UNESP]; Grilli, Eleonora; Murgia, Ilenia; Capra, Gian Franco (Elsevier, 2020)
Brazilian roundwood industry is one of the most important and productive in the world, with Eucalyptus plantations alone representing 73% of the total planted forests. Deep rooting in these plantations represents a more common phenomena than generally expected. However, there is still a lack of information on environmental factors that drive root growth in deep soil layers, with particular emphasis on edaphoclimatic conditions, and related consequence in terms of soil water behavior. As a part of a larger project, this research aimed to investigate soil water and fine root system distribution in deep tropical soils under a commercial Eucalyptus plantation chronosequence. Along a 2800-km gradient (from south- to north-east Brazil), 14 experimental areas were planted with a “plastic” clone (E. urophylla) and investigated in terms of climatic conditions, soil and water features, and plant/stand development for an entire 6-years rotation period. Fine roots distribution were investigated in one site (in Brazil) till to 20 m deep at 3, 9, 24, 48, and 65 months after planting. Results showed a fast displacement of the root front down to 75, 325, 825, 1250, and 1575 cm at month 3, 9, 24, 48, and 65 after planting, respectively. Fine root densities (g cm−3) and proportional water capture exponentially decreased with soil depth. Deep fine roots showed a relativelly higher efficiency in acquiring water than the shallower, denser roots. The relationship between stand height vs root front depth followed an exponential trend, suggesting that these stands developed relatively faster in height rather than in depth during the first 48 months, with the opposite characterizing plantation afterwards. Regardless of stand age, E. urophylla trees rapidly explored a considerable volume of soil at a relatively limited carbon cost. Multivariate statistics showed that edaphoclimatic conditions play a major role in Eucalyptus plant/stand development. This study outlined the major role played by soil development. From poorly developed sandy Entisols, to medium developed Inceptisols, and to most developed fine textured Oxisols, both plant growth and stand productivity greatly improved accordingly. This study suggests that soil type, together with other environmental factors, are likely to influence both the development and behavior of Eucalyptus plantations for an extent greater than commonly anticipated.
Keywords: Deep rooting; Entisols; Eucalyptus urophylla; Oxisols; Soil development